School Motivation, Emotional Intelligence and Academic Performance in Students of Secondary Education - Usán Supervía., Pablo (2018)
The aim of this study was to analyze the relationship between school motivation, emotional intelligence and academic performance in a sample of 3512 adolescent students belonging to 18 educational centers. The instruments used were the spanish versions of the Educational Motivation Scale (EME-S), the Traid Meta-Mood Scale-24 (TMMS-24) and the academic performance was quantified through the average grade of the students. The results showed stronger relationships between intrinsic school motivations and emotional intelligence than extrinsic motivations and amotivation. Likewise, emotional regulation, intrinsic motivation and demotivation predicted students’ school performance. The influence of school motivation, emotional intelligence and academic performance in the personal and academic development of the students.